"Social Stuff" and Institutional Micro-Processes: Alcohol Use by Students in Australian University Residential Colleges. (September 2015) - Leontini, Rose; Schofield, Toni; Lindsay, Jo; Brown, Rebecca; Hepworth, Julie; Germov, John
The literature on alcohol consumption among university and residential college students in Australia and comparable countries shows a high incidence of heavy and/or frequent drinking. In this article, we report the findings from a study on alcohol consumption among undergraduate university students living in residential colleges in Australia. The aim of the study was to examine residents' alcohol use as part of a broader set of institutional practices in higher education that are constructed as central to the student experience. The data were collected through in-depth semistructured interviews with 29 students from seven residential colleges. We found that inclusion of alcohol in many students' social and extracurricular activities while residing in college is associated with heavy and/or frequent drinking. We suggest that the use of alcohol among students is shaped by the colleges' institutional micro-processes, leading to a tension between college managements' aim to foster alcohol citizenship and students' liberty to engage in frequent and/or heavy drinking.